Pengomposan Tandan Kosong Kelapa Sawit yang Ditambahkan Berbagai Jenis Kotoran Hewan Ternak dan Penentuan Kualitas Kimia Bokashi Berbasis Standar Nasional Indonesia - Yunda, Alifia Dearta; Saputra, Riza Adrianoor; Sari, Nukhak Nufita (Jurnal Agro Industri Perkebunan, 2023)
Oil palm empty fruit bunch (OPEFB) is a large amount of palm oil industry waste and has the potential to be used as bokashi fertilizer with the addition of livestock manure to enrich its nutrient content. This study aims to determine the chemical quality of OPEFB bokashi by adding each chicken, cow, and goat manure based on the quality standards of organic fertilizer INS-19-7030-2004. The research was conducted from June to August 2022 in Tanah Bumbu Regency, South Kalimantan, and the Soil Laboratory of the Department of Soils, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Kalimantan. This study used a quantitative method (nutrient analysis in the laboratory). The following treatments were used: K0 = OPEFB without adding livestock manure, K1 = OPEFB with adding chicken manure, K2 = OPEFB with adding cow manure, and K3 = OPEFB with the addition of goat manure. The results showed that treatment K1 (bokashi OPEFB with chicken manure) had better chemical quality than treatments K0, K2, and K3, namely parameters organic C (13,72%), total N (0.92%), C/N ratio (14.91%), total P (1.00%), total K (0.60%), total Ca (6.56%), and total Fe (0.02%). However, the total Mg parameter in the K1 treatment was 1.36% above the maximum SNI limit, and the pH parameters in all treatments (K0 4.91, K1 5.89, K2 4.59, and K3 5.05) were not in accordance with SNI-19-7030-2004.